Interplay Between the Intestinal Microbiota and Acute Graft-Versus-Host Disease: Experimental Evidence and Clinical Significance - Hong, Tao; Wang, Rui; Wang, Xiaoqi; Yang, Shijie; Wang, Weihao; Gao, Qiangguo; Zhang, Xi (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative therapy for many hematological malignancies and deficiencies in addition to other immune diseases, but acute graft-versus-host disease (aGVHD) has remained a major obstacle that limits allo-HSCT and exhibits a daunting mortality rate. The gut is one of the organs most severely affected by this severe complication. The enormous quantity of intestinal microbiota constituents living in the host intestinal tract has been proven to be closely associated with immune homeostasis and diseases, including aGVHD, but the nature of this relationship remains unclear. Because of the great impact on the intestinal microbiota caused by allo-HSCT and aGVHD, alterations in host intestinal commensals post-transplant have been actively investigated. The current animal and human studies investigating the intestinal microbiota in aGVHD and the understanding of the influence and management of the microbiota in the clinic are reviewed herein. Remodeling the intestinal microecology may provide us with novel strategies for preventing and treating aGVHD in the intestinal tract, with great clinical benefits.